The Effects of Kersen Juice (Mutingia calabura L.) and Lakum Leaf Extract (Cayratia trifolia L.) on Lipid Profile of White Rats (Rattus norvegicus L.) Hyperlipidemia - Sopandi, Didin; Saraswati, Tyas Rini; Yuniwarti, Enny Yusuf Wachidah (Bioedukasi: Jurnal Pendidikan Biologi, 2019)
Kersen fruit and Lakum leaf contain substances that are potential as an antihyperlipidemic. This study aimed to analyze The Effects of Kersen Juice (Mutingia calabura L.) with dosage 0.2 ml/200 g BW and Lakum Leaf Extract (Cayratia trifolia L.) with dosage 40 mg/200 g BW on Lipid Profile of White Rats (Rattus norvegicus L.) Hyperlipidemia. This study used a complete randomized design (CRD). Twenty adult male Wistar rats were divided into five groups, P0 as a control group, P1 as a HFD control group, P2 as a HFD group treated with Kersen juice with dosage 0.2 ml/200 g BW, P3 as a HFD group treated with Lakum leaf extract with dosage 40 mg/200 g BW and P4 as a HFD group treated by simvastatin. The treatments were given orally for 28 days. The parameters of this study were cholesterol level, HDL, LDL, triglyceride, body weight, and food consumption. One way ANOVA test was performed to determine the significant differences p<0.05 between groups followed by Duncan test with a 95% significant level. The results showed that compared to Kersen juice with dosage 0.2 ml/200 g BW, administration of Lakum leaf extract with dosage 40 mg/200 g BW was more effective in lowering cholesterol level, triglyceride and increasing HDL level, however, they were not effective in lowering LDL in rats with hyperlipidemia